Structural and Optical Properties of Chemically Synthesized Cu2ZnSnS4 (CZTS) Nanoparticles - A.A., Ajayi; A.B., Alabi; S. I., Akinsola; O. A., Babalola; J.T., Adeleke (Covenant Journal of Physical and Life Sciences, 2018)
The structural and optical properties of Cu2ZnSnS4 nanoparticles prepared by an affordable chemical route were investigated with the aim of determining suitability of the nanoparticles for photovoltaic applications. XRD characterization indicates phases that exhibit kesterite structure of CZTS. The crystallite sizes calculated for both CZTS nanoparticles specimen were comparable to those reported in literature. The absorbance was found to be considerably high within the visible region of the electromagnetic radiation while the transmittance was very low. Theoretical band-gap was calculated to be between 1.55 eV and 1.92 eV which are the ideal band-gap for solar cell absorber for high conversion efficiency.